Factors influencing seed cotton marketing decisions by smallholder farmers in Zimbabwe - Maxmore, Njanji; Cosmas, Parwada (International Journal of Sustainable Agricultural Research, 2024)
Economic reforms such as the liberalization of export and processing-linked marketing channels have encouraged farmers to produce more. Unfortunately, cotton production in Zimbabwe has been declining regardless of such interventions. Why is the production declining despite these interventions including the government-free inputs and supported extension services? Cotton marketing is one of the main factors that influence overall quantities of a commodity to be produced but the practices and behavior of farmers are relatively unknown and unpredictable in the cotton markets. Therefore, this study was to explore factors influencing smallholder farmers' cotton marketing decisions in three cotton-producing provinces of Zimbabwe. A representative sample of 1080 cotton farmers were randomly selected from these provinces and a double hurdle model was used to evaluate market participation and intensity guided by probit model and censored tobit model respectively. Results showed that the decision to participate in cotton marketing was exclusively influenced by experience in cotton production while the intensity of cotton marketing was exclusively influenced by household labour and access to information. Market prices did not significantly (P<0.05) influence both the participation and intensity of cotton markets. The source of inputs and affiliation to marketing associations influence both marketing decisions. It is recommended that the government of Zimbabwe should revise the existing cotton marketing policies to encourage many buyers into cotton markets. The establishment of cotton marketing hubs can increase cotton marketing participation and intensity through increased access to decentralised marketing options.